Lipolytic activity in free and immobilized cells of Phoma glomerata - Pollero, Ricardo José (1997)
The lipolytic activity of free and immobilized whole cells of the pathogenic fungus Phoma glomerata was demonstrated, and several properties of the lipase involved were determined. Free fungal cells and small pieces of immobilized cells, prepared by spontaneous colonization on a solid surface or entrapped in calcium alginate, were incubated with triolein in buffered medium. Different incubation conditions were assayed to optimize the reaction, to determine the effects of heating and time on stability of the immobilized preparations and the time course of the reactions. Although the enzyme cleaves all ester bonds of triolein, it shows some preference for the outer bonds. An optimal pH of 7.5–8.0, optimal temperature of 45°C for free and 50°C for immobilized cell preparations, the necessity for substrate emulsifiers, and reaction independence from calcium and magnesium were demonstrated. Results suggest that immobilized whole cells of P. glomerata would be a suitable tool to study its lipid physiology and to explore further the possible biotechnological use of its lipase activity.